Privacy Concerns due to Class Elements in Cloud Environments despite Full Homomorphic Encryption - Jaber, Aws Naser; Mazlina, Abdul Majid; Kamal Z., Zamli; Mohamad Fadli, Zolkipli
Cloud computing signifies a structural shift towards zero clients and traditionally integrated computational supplies. Because cloud computing does not provide the client with complete governance over the cloud, concerns have surfaced pertaining to data confidentiality, particularly to the misuse or unauthorised access of crucial data by service providers. In response to these concerns, cryptography has been suggested as an apparently effective measure. Recently, fully homomorphic encryption (FHE)—often regarded as the ‘Holy Grail’ of encryption owing to its potency—has been understood to provide a completely functional paradigm with encouraging prospects for supporting privacy in the cloud. However, in this paper, we argue that cryptography alone, even with extremely potent tools such as FHE, cannot offer the level of privacy needed in normal cloud computing environments. Moreover, we explain that a pyramid of natural class elements is present in private cloud programs, and demonstrate that no cryptographic tools can implement rules within classes where data are shared between multiple clients. In conclusion, we stress that to ensure data privacy, consumers of cloud computing services should consider alternative strategies, such as unbreakable hardware, complex trust ecosystems, and distributed computing.